Wings over the Geoid: Employing Airborne Gravity Data in Geoid Determination - Timilsina, Sushmita (Journal of Land Management and Geomatics Education, 2025)
This study focuses on the application of airborne gravity data to develop a regional geoid model of Nepal in the Remove-Compute-Restore (RCR) framework. In the scenario of difficulties presented by the rugged landscape of Nepal and the limited availability of terrestrial gravity data, airborne gravity measurements serve as an effective input dataset for geoid modeling. The research utilizes the XGM2019e for the reduction of long-wavelength signal reduction and employed LSC to compute geoid residuals, with model covariance functions established from spherical harmonic degree variances. Although greater discrepancies are observed in mountainous areas and near national borders due to the scarcity of data, the findings indicate reasonable geoid residuals, especially inside the boundary. The study suggested that higher-resolution airborne gravity surveys can be a feasible and economical approach for geoid determination in areas such as in Nepal that are either inaccessible or lack sufficient data.